Evaluating Mathematical Problem-Solving Skills in Primary School Students: Challenges and Insights from Polya’s Framework - Rahmayati Nur Hidayah; Rahayu Condro Murti (STAI Hubbulwathan Duri, 2025)
Mathematical problem-solving skills are fundamental for fostering critical thinking, creativity, and the ability to address real-life challenges. However, many primary school students struggle with applying these skills effectively. This study aims to analyze the mathematical problem-solving abilities of Grade V elementary students using Polya’s four-stage problem-solving model. This qualitative descriptive research involved 56 Grade V students from a primary school. Data were collected using a mathematical problem-solving test focused on numerical material. Students' responses were analyzed based on Polya’s stages: understanding the problem, devising a plan, carrying out the plan, and looking back. The data analysis included data collection, reduction, presentation, and verification. The findings revealed that students showed the highest proficiency in understanding the problem (37%), followed by planning the solution (30%), solving the problem (23%), and rechecking their work (17%). These results indicate a declining trend in performance as students progress through each problem-solving stage. The study highlights students’ limited abilities in applying strategic and reflective thinking, particularly in later stages of the problem-solving process. This suggests a need for instructional approaches that promote active engagement, systematic thinking, and creative problem-solving. Educators are encouraged to adopt learning models that support student-centered learning and facilitate the development of higher-order thinking skills.